Implementasi Penggunaan Metode Iqro’ Dalam Mengenalkan Bacaan Al-Qur’an Pada Siswa Di SDN Banaran Pulung Ponorogo - Ida MartafiaPutri; Kayyis FithriAjhuri (Jurnal Pendidikan Educandum, 2026)
This study aims to analyze the implementation of the Iqro’ method in introducing Qur’anic reading to students at SDN Banaran Pulung Ponorogo and to assess its effectiveness in improving reading skills. Using a library research approach, the study focused on early-grade elementary students participating in Qur’anic reading and writing extracurricular activities. The Iqro’ method was applied gradually, starting from the introduction of hijaiyah letters to reading verses with basic tajweed. Its strength lies in systematically structured materials that are well-suited for elementary-level learners. Challenges encountered include limited study time and varying student abilities. Overall, the Iqro’ method proved effective in building foundational Qur’anic reading skills, especially when supported by teachers and adequate learning resources. Comprising six volumes, the method is taught step by step according to students’ abilities, with lessons conducted three times a week under direct teacher guidance. Its systematic, simple, and practical nature makes it appropriate for elementary-level instruction, though obstacles such as time constraints and differences in student proficiency remain.